THE CAUSAL RELATIONSHIPS MODEL FOR POTENTIAL SMART TOURISM DEVELOPMENT OF RESTAURANT ENTREPRENEURS IN THAILAND TO SUPPORT CHINESE FIT TOURISTS - Pramtip Chompucum; Vuttichat Soonthonsmai; Sakchai Setarnawat, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study examined the consistency of structural equation modelling showing the hypothesis of the influence of service marketing mix and the application of smart tourism on restaurant entrepreneurs' business performance in Thailand through service quality and empirical data. The sample group consisted of 230 entrepreneurs of small food and beverage businesses in Thailand, serving Chinese FIT tourists. A questionnaire was used to collect data as well as statistical analysis, mean, standard deviation, and creating a causal relationship model of service marketing mix affecting the business performance of restaurant entrepreneurs in Thailand through service quality with linear structural relationships. The results revealed that the developed model was consistent with the empirical data. The service marketing mix had no direct influence on entrepreneurs' business performance, but the service marketing mix had an indirect influence on entrepreneurs' business performance through service quality with statistical significance at .01. While the application of smart tourism had direct influence and had an indirect influence on entrepreneurs' business performance through service quality with statistical significance at .01.